Empowering Posyandu Cadres Through Positive Parenting Psychoeducation to Safeguard Children From Stunting - Afiatin, Tina; Nurvita, Sofia; Reginasari, Annisa (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2024)
Indonesia’s demographic bonus for the millennial generation is starting to increase. However, the quality of nutrition and health of Indonesian children is threatened by cases of stunting in several regions in Indonesia without specialized assistance from posyandu cadres as the frontline educators for parents. This community service research aimed to explore posyandu cadres' understanding of the value of positive parenting to prevent stunting through a Psychoeducation Program design. This activity program involved psychoeducational interventions using lectures, discussion, and role-play of positive parenting practices. The Positive Parenting Psychoeducation Activities were carried out involving 39 Posyandu Cadres in Ringu Rara Village, Lamboya Sub-District, West Sumba District, East Nusa Tenggara Province (N = 20) and Posyandu Cadres in Tirtoadi Village, Mlati Sub-District, Sleman District, Special Region of Yogyakarta Province (N = 19). A psychoeducation program evaluation using the open-ended questionnaire was administered before (pre-test) and after (post-test) lecture sessions, discussion sessions, and Positive Parenting training sessions. Subsequently, the trainers continued with Focused Group Discussion sessions for the follow-up stage of the training. Using a qualitative approach to thematic analysis techniques and cross-tabulations, the authors searched for themes that emerged from the questionnaire responses data and recorded focus group discussion transcripts. Besides, the data organization was also carried out with the help of the MAXQDA 2020 Application. The thematic analysis results generated three main themes around Positive Parenting Psychoeducation activities, namely Posyandu Cadres with their tasks and challenges, Positive Parenting to prevent stunting, and Positive Parenting Psychoeducation follow-up plans. The conclusion drawn from the results of this activity was that the family-household factor of parenting patterns can influence stunting. Posyandu cadres need positive parenting psychoeducation to be able to share information with, assist, monitor, and help parents of children with stunting indications.